Inhibition of the Prefrontal Projection to the Nucleus Accumbens Enhances Pain Sensitivity and Affect - Zhou, Haocheng; Martinez, Erik; Lin, Harvey H.; Yang, Runtao; Dale, Jahrane Antonio; Liu, Kevin; Huang, Dong; Wang, Jing (Frontiers in Cellular Neuroscience, 2018)
Cortical mechanisms that regulate acute or chronic pain remain poorly understood. The prefrontal cortex (PFC) exerts crucial control of sensory and affective behaviors. Recent studies show that activation of the projections from the PFC to the nucleus accumbens (NAc), an important pathway in the brain’s reward circuitry, can produce inhibition of both sensory and affective components of pain. However, it is unclear whether this circuit is endogenously engaged in pain regulation. To answer this question, we disrupted this circuit using an optogenetic strategy. We expressed halorhodopsin in pyramidal neurons from the PFC, and then selectively inhibited the axonal projection from these neurons to neurons in the NAc core. Our results reveal that inhibition of the PFC or its projection to the NAc heightens both sensory and affective symptoms of acute pain in naïve rats. Inhibition of this corticostriatal pathway also increased nociceptive sensitivity and the aversive response in a chronic neuropathic pain model. Finally, corticostriatal inhibition resulted in a similar aversive phenotype as chronic pain. These results strongly suggest that the projection from the PFC to the NAc plays an important role in endogenous pain regulation, and its impairment contributes to the pathology of chronic pain.